Dashboard of Sentiment in Austrian Social Media During COVID-19 - Pellert, Max; Lasser, Jana; Metzler, Hannah; Garcia, David (Frontiers in Big Data, 2020)
To track online emotional expressions on social media platforms close to real-time during the COVID-19 pandemic, we build a self-updating monitor of emotion dynamics using digital traces from three different data sources in Austria. This enables decision makers and the interested public to assess dynamics of sentiment online during the pandemic. We use web scraping and API access to retrieve data from the news platform derstandard.at, Twitter and a chat platform for students. We document the technical details of our workflow in order to provide materials for other researchers interested in building a similar tool for different contexts. Automated text analysis allows us to highlight changes of language use during COVID-19 in comparison to a neutral baseline. We use special word clouds to visualize that overall difference. Longitudinally, our time series show spikes in anxiety that can be linked to several events and media reporting. Additionally, we find a marked decrease in anger. The changes last for remarkably long periods of time (up to 12 weeks). We discuss these and more patterns and connect them to the emergence of collective emotions. The interactive dashboard showcasing our data is available online at http://www.mpellert.at/covid19_monitor_austria/. Our work is part of an web archive of resources on COVID-19 collected by the Austrian National Library.